Effect of Varying Light Intensity on Welfare Indices of Broiler Chickens Grown to Heavy Weights - Olanrewaju, H.A.; Miller, W.W.; Maslin, W.R.; Collier, S.D.; Purswell, J.L.; Branton, S.L. (International Journal of Poultry Science, 2011)
The effects of varying light-intensity on ocular, immune, fear and leg health of broiler chickens grown to heavy weights under environmentally controlled conditions were evaluated. Four identical trials were conducted with two replications per trial. In each trial, 600 Ross 308 chicks were randomly distributed into 10 environmentally controlled chambers (30 males and 30 females chicks/chamber) at 1 d of age. Each chamber was randomly assigned one of five light intensities (25, 10, 5, 2.5 and 0.2 lx) from d 22 to 56 d of age. Feed and water were provided ad libitum. Humoral immune response was determined on d 28, while ocular health and general well-being assessments were performed on d 42 and 49, respectively. Results indicated that total Anti-Sheep Red Blood Cells (SRBC) antibody was not significantly (p>0.05) affected by the treatments, but there was significant (p<0.05) sex effects under 25 and 2.5 lx treatments. There were no differences among treatments for either ocular weight relative to BW, ocular assessments, gait scoring test or tonic immobility responses, suggesting that these levels of light intensities did not compromise welfare of the birds. This study shows the positive impact on profits to commercial poultry facilities that are using low lighting environment to reduce hyperactivity, pecking damage and energy costs without compromising the welfare of the broilers.